2012
DOI: 10.2485/jhtb.21.399
|View full text |Cite
|
Sign up to set email alerts
|

TMJ Degenerative Changes in SAMP3 Mice by Occlusal Disharmony and Aging

Abstract: Aging and mechanical loading by occlusal disharmony are critical and etiological factors for the onset of temporomandibular joint disorders (TMDs). Senescence-accelerated mouse prone 3 (SAMP3) is one of the animal models for studying age-related degenerative changes of various tissues and organs. To evaluate the influences of both the aging and/or the mechanical loading induced by occlusal disharmony on the SAMP3 TMJ condyle, histological and immunohistochemical analyses were performed.Fifty-five, 4-week-old S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To date, it is no doubt that Wnt/b-catenin signaling pathway plays an important role in the development and maintenance of cartilage, [13][14][15][16] but its detailed function is still controversial and sometimes apparently contradictory. Previous studies have demonstrated that Wnt signaling is persistently active in normal adult chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, it is no doubt that Wnt/b-catenin signaling pathway plays an important role in the development and maintenance of cartilage, [13][14][15][16] but its detailed function is still controversial and sometimes apparently contradictory. Previous studies have demonstrated that Wnt signaling is persistently active in normal adult chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that Wnt signaling was active in several cell types including chondrocytes, osteoblasts, and osteocytes, they appear to use the Wnt/β‐catenin pathway to transmit signals of mechanical loading to cells . Furthermore, Wnt signaling pathway plays regulatory roles in the development and maintenance of cartilage, and is also involved in TMJ (Temporomandibular Joint) disease . Both constitutive up‐ or downregulation of the canonical Wnt pathway negatively influence cartilage development and maintenance, resulting in OA‐like features .…”
mentioning
confidence: 99%
See 1 more Smart Citation